Teach yourself visually ipad - Watson, Lonzell (Visual read less, learn more, 2010)
Provides you with the ultimate visual learning guide for the ultimate visual computing device: the Apple iPad. Demonstrates how to get the most from the iPad's unparalleled ability to offer amazing graphics, crisp audio, and light-weight portability